ANALYSIS OF STRESS INTENSITY FACTOR BASED ON GENERALIZED MIXED ENRICHED ELEMENT METHOD - GUO Shuai; QING GuangHui; HE YuXuan (Jixie qiangdu)
The stress intensity factor (SIF) have been studied by many methods based on the displacement element model. However, under sparse meshes, the displacement element models will suffer from excessive stiffness, and are difficult to introduce the stress boundary conditions directly which lacking in objectivity. The generalized mixed enriched element method is proposed based on the principle of enriched element and generalized H-R variational principle. This method takes the crack tipstress singularity into account, considers the introducing of stress boundary conditions, and overcomes the oscillation of the classical mixed enriched element method. Numerical examples show that the stress intensity factor obtined by this method is stable and reliable with a high degree of accuracy.